Intolerance of Uncertainty and Psychological Distress Experienced by the First Batch of Students in the Newly Established Study Program - Novita, Putri; Rahayu, Maria Nugraheni Mardi (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Students experience symptoms of psychological distress such as difficulty sleeping, irregular eating patterns, irritability, difficulty concentrating, and feeling uneasy. The purpose of this study was to determine the relationship between intolerance of uncertainty and psychological distress in college students. The research method used was quantitative with correlational analysis, with a total of 35 participants who were first batch students of the Counseling Guidance study program at an Institute in city X. Data was collected using the DASS 42 scale with a Cronbach alpha value of 0.9483 and an intolerance scale uncertainty with a cronbach alpha value of 0.833. Based on the Pearson product moment correlation test, it is known that the value of r = 0.515 with a Sig value = 0.001 (p <0.05) means that there is a significant relationship between intolerance uncertainty and psychological distress. The higher the intolerance uncertainty, the higher the psychological distress felt by students. This research is useful for students so they don't have to worry too much about an uncertain future so they can avoid symptoms of psychological distress that can interfere with individual life.Mahasiswa mengalami gejala-gejala psychological distress seperti kesulitan tidur, pola makan tidak teratur, mudah marah, sulit berkonsentrasi, dan merasa tidak tenang. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara intolerance of uncertainty dengan psychological distress pada mahasiswa. Metode penelitian yang digunakan yaitu kuantitatif dengan analisis korelasional, dengan jumlah 35 orang partisipan yang merupakan mahasiswa angkatan pertama program studi Bimbingan Konseling pada sebuah Institut di kota X. Pengambilan data dilakukan dengan menggunakan skala DASS 42 dengan nilai alpha cronbach sebesar 0,9483 dan skala intolerance uncertainty dengan nilai alpha cronbach sebesar 0,833. Berdasarkan uji korelasi product moment pearson diketahui nilai r = 0,515 dengan nilai Sig = 0,001 (p < 0,05) maka artinya ada hubungan yang signifikan antara intolerance uncertainty dengan psychological distress. Semakin tinggi intolerance uncertainty maka akan semakin tinggi juga psychological distress yang dirasakan mahasiswa. Penelitian ini berguna bagi mahasiswa agar tidak perlu khawatir secara berlebihan mengenai masa depan yang tidak pasti sehingga dapat terhindar dari gejala-gejala psychological distress yang bisa mengganggu kehidupan individu.